2020
DOI: 10.1021/acs.analchem.9b05761
|View full text |Cite
|
Sign up to set email alerts
|

Charge Distribution between Different Classes of Glycerophospolipids in MALDI-MS Imaging

Abstract: Matrix-assisted laser desorption ionization mass spectrometry imaging (MALDI-MSI) is widely used to visualize and analyze the distribution of membrane lipids in an increasingly large number of applications. In this context, different lipoforms of glycerophospholipids (GPLs) are among the prime targets of interest. For this group of analytes, however, ion suppression effects have been described to strongly favor the detection of certain GPL classes over others, thereby hampering the analysis of suppressed speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
88
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 60 publications
(89 citation statements)
references
References 56 publications
1
88
0
Order By: Relevance
“…With more complex samples as with tissue homogenates, ion suppression effects based on lipid class may affect ion yield. 43 While NOR performed well with MALDI-2, DHB had the highest increase in lipids detected with MALDI-2 from the tissue homogenates compared with other matrices. The number of lipids detected in each lipid class for DHB and NOR is displayed in is optimal for non-polar lipid studies and DHB is better applied to increased sensitivity of phospholipids.…”
Section: Lipidomic Comparisons Across Multiple Tissue Typesmentioning
confidence: 90%
See 1 more Smart Citation
“…With more complex samples as with tissue homogenates, ion suppression effects based on lipid class may affect ion yield. 43 While NOR performed well with MALDI-2, DHB had the highest increase in lipids detected with MALDI-2 from the tissue homogenates compared with other matrices. The number of lipids detected in each lipid class for DHB and NOR is displayed in is optimal for non-polar lipid studies and DHB is better applied to increased sensitivity of phospholipids.…”
Section: Lipidomic Comparisons Across Multiple Tissue Typesmentioning
confidence: 90%
“…Data presented in Table 1 shown that MALDI-2 may correct for ion suppression effects to enable detection of these protonated species. 43 MALDI-2 increased protonated lipid coverage with all matrices but the species detected with MALDI-2 varied based on the matrix. The TG species, for example, was detected only with MALDI-2 for CHCA, DHB, and NOR but was not detected with DHA.…”
Section: Analysis Of Lipid Standardsmentioning
confidence: 94%
“…MSI lipid class coverage in the mouse cerebellum. As the ionization of many lipid classes suffers from a known suppression effect, 47 the coverage of lipid classes in mouse cerebellum tissue was evaluated to assess the suitability of BzPy for comprehensive lipid coverage in MSI studies. In total, 508/365 lipids were annotated in the positive/negative ion mode, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…In the context of membrane lipids, PC has been reported to heavily suppress all other GPL classes in the positive ion mode [16]. Recently published results by Boskamp and Soltwisch describe additional ISE between other GPL classes and also point out an inverse ion promotion effect, where the presence of a second GPL boosts ion signal intensity [15]. A variation of strongly suppressing or promoting molecular species between different types of tissue could therefore be the root cause of the observed bias in intensity response.…”
Section: Ion Suppression Effectsmentioning
confidence: 99%
“…fraction of desorbed molecules is ionized [6][7][8][9][10][11][12][13]. Ion yields strongly depend on the chemical properties of the matrix and the analyte itself but also on the overall composition of the sample [12,14,15]. For glycerophospholipids (GPL), for example, it has been shown that the presence of small quantities of phosphatidylcholine (PC) can effectively quench ion yields for other GPL classes like phosphatidylethanolamine (PE) [15,16].…”
Section: Electronic Supplementary Materialsmentioning
confidence: 99%